Contribució al coneixement florístic de l'Alta Ribagorça i la Vall d'Aran - Ballesteros, Enric (Institució Catalana d'Història Natural, 1989)
Some records of vascular flora from the Alta Ribagorca and the Vall d'Aran regions are commented, with indications about their habitat. Draba fladnizensis Wulf. in Jacq., a species with arctic-alpine distribution, known from French Pyrenees, is reported for the first time from Spain. The record of Saxifraga retusa Gouan in the Besiberri's mountains is the western most limit of this species distribution area. Peer reviewed